Participation and performance trends of East-African runners in Swiss half-marathons and marathons held between 2000 and 2010 - Cribari, M.; Rüst, C. A.; Rosemann, T.; Onywera, V.; Lepers, R.; Knechtle, B. (BMC Sports Science, Medicine and Rehabilitation, 2013)
Background: This study examined the changes in participation, performance and age of East African runners competing in half-marathons and marathons held in Switzerland between 2000 and 2010. Methods: Race times, sex, age and origin of East African versus Non-African finishers of half-marathon and marathon finishers were analyzed. Results: Across time, the number of Kenyan and Ethiopian finishers remained stable (P > 0.05) while the number of Non-African finishers increased for both women and men in both half-marathons and marathons (P < 0.05). In half-marathons, the top ten African women (71 +/- 1.4 min) and top three (62.3 +/- 0.6 min) and top ten (62.8 +/- 0.4 min) African men were faster than their Non-African counterparts (P < 0.05). In marathons, however, there was no difference in race times between the top three African men (130.0 +/- 0.0 min) and women (151.7 +/- 2.5 min) compared to Non-African men (129.0 +/- 1.0 min) and women (150.7 +/- 1.2 min) (P > 0.05). In half-marathons and marathons was no difference in age between the best Non-African and the best African runners (P > 0.05). Conclusions: During the last decade in Switzerland, the participation of Kenyan and Ethiopian runners in half- and full- marathons remained stable. In marathons there was no difference in age and performance between the top African and the top Non-African runners. Regarding half-marathons, the top African runners were faster but not younger than the top Non-African runners. Future insight should be gained by comparing the present results with participation, performance and age trends for East African runners competing in marathons held in larger countries.